2003
DOI: 10.1016/s0896-6273(03)00531-2
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter Modulation of Slow, Activity-Dependent Alterations in Sodium Channel Availability Endows Neurons with a Novel Form of Cellular Plasticity

Abstract: Voltage-gated Na+ channels are major targets of G protein-coupled receptor (GPCR)-initiated signaling cascades. These cascades act principally through protein kinase-mediated phosphorylation of the channel alpha subunit. Phosphorylation reduces Na+ channel availability in most instances without producing major alterations of fast channel gating. The nature of this change in availability is poorly understood. The results described here show that both GPCR- and protein kinase-dependent reductions in Na+ channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(188 citation statements)
references
References 48 publications
6
180
1
1
Order By: Relevance
“…Despite evidence that neurons possess a considerable reserve of Na v channels (Madeja, 2000), reductions in Na v channel availability during repetitive firing or pharmacological manipulation influence AP generation (Fleidervish et al, 1996;Colbert et al, 1997;Jung et al, 1997;Madeja, 2000;Colbert and Pan, 2002;Carr et al, 2003). In support of this principle, a 47% reduction in Na v channel availability in STN neurons with 5 nM TTX did not abolish pacemaking but did reduce its frequency and depolarized APth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite evidence that neurons possess a considerable reserve of Na v channels (Madeja, 2000), reductions in Na v channel availability during repetitive firing or pharmacological manipulation influence AP generation (Fleidervish et al, 1996;Colbert et al, 1997;Jung et al, 1997;Madeja, 2000;Colbert and Pan, 2002;Carr et al, 2003). In support of this principle, a 47% reduction in Na v channel availability in STN neurons with 5 nM TTX did not abolish pacemaking but did reduce its frequency and depolarized APth.…”
Section: Discussionmentioning
confidence: 99%
“…Among the properties that discriminate slow from fast inactivation (Hodgkin and Huxley, 1952;Rudy, 1978;Kuo and Bean, 1994;Martina and Jonas, 1997;Ellerkmann et al, 2001) are the kinetics of recovery from inactivation. For the slow inactivated state, recovery occurs with a time constant of several seconds, which is several orders of magnitude slower than the recovery from fast inactivation (Kuo and Bean, 1994;Ellerkmann et al, 2001;Carr et al, 2003;Do and Bean, 2003). After GABAergic IPSPs, APs were modified in a manner that suggested that there was a transient increase in Na v channel excitability.…”
Section: Gaba a Ipsps Recover Na V Channels From Inactivationmentioning
confidence: 99%
“…The peak currents (I) were normalized relative to the maximal values (I max ) obtained at a HP of -140 mV and plotted against the conditioning pulse potential. Data were fit to a modified Boltzmann equation: 42,43 I/I max = (1 -I resid )/[1 + exp(-(V -V ½ )/k)]…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Voltage-gated sodium channels are regulated by G-protein-coupled receptor (GPCR)-mediated phosphorylation (for review, see Cantrell and Catterall, 2001). Dopamine (Surmeier et al, 1992;Ma et al, 1994;Cantrell et al, 1997;Cantrell et al, 1999) and serotonin (Carr et al, 2003) modulate the generation of sodium spikes. However, it was not known whether EPSP amplification by sodium channels is affected by GPCR activation.…”
Section: Dopamine and Bright Light Contribute To Network Adaptation Bmentioning
confidence: 99%